Lets find the slope first:
Slope (m) is change in y's by change in x's
Change in y: -7 - - 10 = -7 + 10 = 3
Change in x: 4 - 2 = 2
Slope = 3/2 (this is m)
So, the equation is:
![\begin{gathered} y=mx+b \\ y=(3)/(2)x+b \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/52glevceg916tj5wg02p3w6fcme1zb3n69.png)
b is the y-intercept.
We can get it by plugging in any point. Let's put (2, -10). So we have:
![\begin{gathered} y=(3)/(2)x+b \\ -10=(3)/(2)(2)+b \\ -10=3+b \\ b=-10-3 \\ b=-13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o851st0unkx0cvugvhigusneem4q8cc8gn.png)
Final equation is:
![\begin{gathered} y=(3)/(2)x+b \\ y=(3)/(2)x-13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/snexgh61apa1zgi9mbwobb5e24jl3ddw2k.png)